Pertumbuhan dan Produksi Karkas Kelinci Rex pada Umur Potong yang Berbeda - Siregar, G. A. W.; Nuraini, H.; Brahmantiyo, B. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2014)
Food diversification need to use other kind livestock which have high biological potency, economic, halal, good nutrition as meat-animal including rabbit. Rex have a medium body size compared with other kinds of frayer. The aim of this research was to determine Rex carcass and non carcass productivity. The research was used completely randomized design with four treatments. Statistical analysis used in this research was Analysisof Covariance Design (ANCOVA). Rex males were used as sample. Rex’s growth, carcass and non carcass productivity were observed. The result showed that slaughter ages had an effect on slaughter weight, carcass weight, meat weight and percentage of meat and bone. The growth of non carcass components such as heads, feets, skins and digestive tracts were affected by slaughter ages. 12 weeks-old Rex produced highest meat percentages from body weight. It was obtained that 12 weeks-old Rex produced optimal growth, slaughter weight and carcass productivity.